2015
DOI: 10.1093/ee/nvv074
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Location, Cropping History, Tillage, and Chlorpyrifos on Soil Arthropods in Peanut

Abstract: Demand for agricultural production systems that are both economically viable and environmentally conscious continues to increase. In recent years, reduced tillage systems, and grass and pasture rotations have been investigated to help maintain or improve soil quality, increase crop yield, and decrease labor requirements for production. However, documentation of the effects of reduced tillage, fescue rotation systems as well as other management practices, including pesticides, on pest damage and soil arthropod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…On the other hand, arthropods are highly responsive to environmental changes, such as fertilizers, pesticides, weed management, cover crop, grazing management, pest management, prey availability, plant composition. Many publications have reported that these cultivation practices have been shown to have an impact on arthropod populations in an agroecosystem: grazing management systems on coleopteran dung beetles (Magdoff and van Es 2021), mulches, and pest management on arboreal arthropod in chili pepper (Herlinda et al 2021), weed management on arthropod communities (Bryant et al 2013), plant composition on arthropod pest and predator abundance (Parry et al 2015), insecticide on not-targeted arthropods (Hanif et al 2020), tillage and chlorpyrifos on soil arthropods (Cardoza et al 2015), insecticides on the abundance of canopy arthropods (Prabawati et al 2019). In addition, Culliney (2013) reported that soil nutrient has an impact on arthropod communities by enhancing arthropod growth, fecundity, survival, and density.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, arthropods are highly responsive to environmental changes, such as fertilizers, pesticides, weed management, cover crop, grazing management, pest management, prey availability, plant composition. Many publications have reported that these cultivation practices have been shown to have an impact on arthropod populations in an agroecosystem: grazing management systems on coleopteran dung beetles (Magdoff and van Es 2021), mulches, and pest management on arboreal arthropod in chili pepper (Herlinda et al 2021), weed management on arthropod communities (Bryant et al 2013), plant composition on arthropod pest and predator abundance (Parry et al 2015), insecticide on not-targeted arthropods (Hanif et al 2020), tillage and chlorpyrifos on soil arthropods (Cardoza et al 2015), insecticides on the abundance of canopy arthropods (Prabawati et al 2019). In addition, Culliney (2013) reported that soil nutrient has an impact on arthropod communities by enhancing arthropod growth, fecundity, survival, and density.…”
Section: Introductionmentioning
confidence: 99%